2019
DOI: 10.3389/fphar.2019.01029
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Drug Trifluoperazine Suppresses Colorectal Cancer by Inducing G0/G1 Arrest and Apoptosis

Abstract: Repurposing existing drugs for cancer treatment is an effective strategy. An approved antipsychotic drug, trifluoperazine (TFP), has been reported to have potential anticancer effects against several cancer types. Here, we investigated the effect and molecular mechanism of TFP in colorectal cancer (CRC). In vitro studies showed that TFP induced G0/G1 cell cycle arrest to dramatically inhibit CRC cell proliferation through downregulating cyclin-dependent kinase (CDK) 2, CDK4, cyclin D1, and cyclin E and upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 61 publications
2
31
0
Order By: Relevance
“…Interestingly, various mechanisms seem to account for the anti-tumor effects of TFP [ 11 , 12 , 13 , 14 , 15 , 18 ]. In addition to inhibiting calmodulin and downregulating AKT activity, TFP was reported to inhibit DNA repair efficiency in cancer cells by decreasing expression of several DNA repair proteins including RAD51 [ 19 , 37 , 38 ], found to be upregulated in PAH cells [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, various mechanisms seem to account for the anti-tumor effects of TFP [ 11 , 12 , 13 , 14 , 15 , 18 ]. In addition to inhibiting calmodulin and downregulating AKT activity, TFP was reported to inhibit DNA repair efficiency in cancer cells by decreasing expression of several DNA repair proteins including RAD51 [ 19 , 37 , 38 ], found to be upregulated in PAH cells [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the development of new compounds, drug repurposing/repositioning has become an attractive strategy to treat cancer and PAH [ 9 , 10 ], taking advantage of the well-known safety and pharmacokinetics profiles of drugs already in use for a disease to treat another illness and, thus, expedite therapies to the clinic. The antipsychotic drug trifluoperazine (TFP) was recently repurposed for cancer treatment due to its anti-tumor activity in various preclinical models [ 11 , 12 , 13 , 14 , 15 ]. Although the exact mechanism of action of TFP remains unclear, TFP was initially shown to inhibit dopamine receptors and functions as an antagonist of calmodulin, a key regulator of calcium-dependent signal transduction critically implicated in vascular smooth muscle cell contraction and proliferation [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…One highly elevated EMT marker in cluster 1 tumors is the signaling protein S100A4, which is a target of the antipsychotic drug trifluoperazine (Figure 7A). It has been shown that trifluoperazine can be repurposed as an anticancer drug and successfully prevent or minimize metastatic spread in different cancers by inhibiting S100A4 through protein oligomerization (55, 56). Targeting S100A4 could also be advantageous for reducing hypoxic signaling in cluster 1 tumors, since it was revealed as HIF1α target (Supplementary File 3).…”
Section: Discussionmentioning
confidence: 99%
“…Trifluoperazine, an anti-psychotic, inhibits cell viability and proliferation, induces apoptosis and promotes cell arrest at G0/G1 phase by repressing CDK2, CDK4, cyclin D1, cyclin E through the increasing p27 expression on HCT116. Also, this effect has a synergized effect with 5-fluorouracil and Oxaliplatin in CT26 and HCT116 colorectal cancer cells (22,23).…”
Section: Colorectal Cancermentioning
confidence: 94%